Pengaruh Literasi Keuangan, Lingkungan Keluarga dan Love Of Money Terhadap Minat Wirausaha Gen-Z Wilayah Kabupaten Sidoarjo - Firdausi, Rajendra Rafi; Panggah Setiyono, Wisnu; Sriyono, Sriyono (Universitas Hamzanwadi, 2024)
Entrepreneurial interest is a person's decision because they feel they have the desire and are interested in pursuing the world of entrepreneurship and have the courage to take risks so that success can be achieved. Generation Z is the generation born in the internet era, so this generation has enjoyed the technological era because it was born in that era. In general, Generation Z was born from 1995 to 2012. This research was conducted to test whether financial literacy, money-loving attitudes and family environment and able to influence the entrepreneurial interest of Gen-Z in the Sidoarjo Regency area. The research was conducted using quantitative techniques with the primary data source being questionnaires to Gen-Z in the Sidoarjo Regency area with a sample of 96 respondents. The results of this research are 1) Financial literacy has an influence on entrepreneurial interest. 2) Family environment has an influence on entrepreneurial interest. 3) Love of Money has an influence on entrepreneurial interest. In deciding to become an entrepreneur or someone who is interested in running an entrepreneur is certainly encouraged by good financial knowledge, family support and a love of money..